Dislocation-driven growth of WS2/WSe2 quantum well superlattices - Yang, Hang; Zeng, Li; Huang, Ziwei; Zhang, Tian; Zhang, Shunhui; Zhang, Xuyang; Ao, Zhikang; Lan, Xiang; Zhang, Baihui (Frontiers in Materials, 2023)
The synthesis of two-dimensional lateral heterojunctions with nanoscale characteristic width as well as sharp interfaces still faces giant difficulties. This means the quantum confinement effects are still hard to be actualized on 2D materials, since widths smaller than 5 nm are requisite that needed for quantum confinement effects and quantum well applications. Here, we realized the growth of a sub-2 nm tungsten sulfide quantum well array in a monolayer of tungsten selenide, driven by the climb of mismatch dislocation in a heterointerface due to the lattice mismatch. The width-controllable 2D quantum well superlattices could be theoretically formed by the mismatch dislocation-driven growth mechanism according to our analysis. Thus, abundant photonic electronic properties can be obtained in 2D quantum well superlattices formed at varied lateral heterointerfaces, which are expected to support the study of topological insulators and superconductors.